PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IVB SD NEGERI 55 KESUMBO AMPAI - Daulay, Derpina Rejekiyah Nur; Syahrilfuddin, Syahrilfuddin; Hamizi, Hamizi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the results of student learning science IVB low grade of primary school 55 Kesumbo Ampai with an average value of 67.14. Therefore, the researchers provide learning alternatives to the application of cooperative learning model TPS in class IVB SD Negeri 55 Kesumbo Ampai. This research aims to improve student learning outcomes IVB Elementary School science class 55 Kesumbo Ampai Application of Cooperative Learning Model TPS. This research is a form of classroom action research (PTK) with 2 cycles. Based on research data anlisis after applying cooperative learning model TPS, the average percentage of the activity of teachers in the first cycle of 62.5% increased to 85.25% in the second cycle. The average percentage of student activity also increased 50% in the first cycle increased to 83.3% in the second cycle. Student learning outcomes in basic score with an average of 67.14 with 50% completion percentage of classes and the first cycle increased with an average value of 75.17 class with an increasing percentage of learning outcomes of 11.96% and the percentage of students who complete 57, 14%. Then the average value silus class II increased to 87.85 with the percentage increase learning outcomes by 30.84% and the percentage of students who completed was 85.71%, after the implementation of cooperative learning model TPS. These results indicate that the implementation of cooperative learning model TPS can improve student learning outcomes Elementary School science class IVB 55 Kesumbo Ampai.Key Words:Learning Model TPS,IPALearning Outcomes